Anatomical description of the skull of the fish Hydrolycus armatus (Jardine & Dchomburgk, 1841) (Characiformes: Cynodontidae) - Almeida Barbosa, Letícia (2026)
Hydrolycus armatus (Jardine & Dchomburgk, 1841), popularly known as peixe-cachorra (dogfish) in the Tocantina region of Maranhão, is a species found in flowing waters and lakes in the state of Maranhão, and plays a significant role in feeding the riverside population and local economy. The objective of this study was to describe the main bones that make up the skull of H. armatus. For this study, the material was dissected and detailed osteological descriptions of the skull were analyzedfrom lateral-dorsal and antero frontal views. Characteristics similar to those described for the species were observed, such as a set of structures located in the upper part, such as the dilator operculi above the parasphenoid, which comprises the outer edge of the inner orbital ring, in addition to robust anterior mandibular dentition that expresses the adaptive specialization of the species in its aquatic environment. This analysis contributes to future studies related to the physiological mechanisms of this fish's life, providing valuable information for investigations into its bone morphology and anatomical studies in the Araguaia-Tocantins basin.